Piezomagnetic effects induced by artificial sources at Mt. Vesuvius (Italy): preliminary results of an experimental survey - R. Napoli; A. Meloni; L. Cafarella; E. Bozzo; E. Armadillo; C. Del Negro; A. Zirizzotti (Annals of Geophysics, 1998)
In order to put new constrains on magnetic effects associated with mechanical stresses, high frequency monitoring of the geomagnetic field was carried out during a seismic tomography experiment (TOMOVES'96 project) at Mt. Vesuvius. Eight proton precession and one Cesium magnetometers were installed along a profile on the SW flank of the volcano to observe possible magnetic changes induced by explosions. Measurements were performed at different sampling frequencies (10 Hz, 0.5 Hz and 0.1 Hz). A remarkable change in the intensity of the magnetic field was observed in only one case. The magnetic transient lasted 12-13 min, reaching the maximum amplitude of slightly less than 15 nT.